Media Sosial dan Jejaring Sosial - Winda Kustiawan; Ade Nurlita; Almaidah Siregar; Syarifah Aini Siregar; Indah Ardianti; Manita Rahma Hasibuan; Sri Agustina (Prodi Perpustakaan dan Sains Informasi, 2022)
This study aims to find out how social media and social networks are developing at this time along with the rise of technology. The strategy used to find out is qualitative, namely looking for various sources such as searching in books, the internet and others. Social media and technological networks take many forms including magazines, internet forums, weblogs, social blogs, microblogging, wikis, podcasts, photos or pictures, videos, ratings and social bookmarking. A social network is a social structure made up of individual or organizational elements. This network shows the way in which they relate because of the similarity of sociality, starting from those who are known everyday to family. Social media and technological networks take many forms including magazines, internet forums, weblogs, social blogs, microblogging, wikis, podcasts, photos or pictures, videos, ratings and social bookmarking. The development of social media is really fast, this can be seen from the large number of members each of these social networking sites has, along with a table of the number of members for each site. Talking on social media seems endless. Several well-known social media sites such as Facebook and Twitter have become a way of life for modern society, both among children, adults and parents who have used these sites a lot. There are even those who are still underage using it.